Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 1-6 - Cumulative Review: 10

Answer

$x = \frac{-1±\sqrt {57}}{2}$

Work Step by Step

$(x+5)(x-4) = -6$ $x(x-4) + 5(x-4) + 6 = 0$ $x^{2} - 4x + 5x - 20 + 6 = 0$ $x^{2} + x - 14 = 0$ $x = \frac{-(1)±\sqrt {1^{2}-4(1)(-14)}}{2(1)}$ $x = \frac{-1±\sqrt {1+56}}{2}$ $x = \frac{-1±\sqrt {57}}{2}$ Check: When $x = \frac{-1+\sqrt {57}}{2}$ $((\frac{-1+\sqrt {57}}{2})+5)((\frac{-1+\sqrt {57}}{2})-4) = -6$ $(8.2749...)(-0.72508...) = -6$ $-6 = -6$ When $x = \frac{-1-\sqrt {57}}{2}$ $((\frac{-1-\sqrt {57}}{2})+5)((\frac{-1-\sqrt {57}}{2})-4) = -6$ $(0.725...)(-8.2749...) = -6$ $-6 = -6$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.